Partisipasi Masyarakat dalam Pengelolaan Sampah Menjadi Gas Metan di Desa Tlekung, Kecamatan Junrejo, Kota Batu - Salma Afifah; Edisty Anindira; Elvara Hana; Haldi Priya; M. Jalaludin; Nur Aini; Nurul Fadlilatus; Satti Wagistina (Universitas Riau, 2021)
Since 2009, Tlekung Village has been used as a Final Disposal Site for rubbish, which has the main problem, namely the problem of the sting smell due to a pile of trash. The purpose of this research is to find out how the TPA Tlekung manages waste and overcomes the problem of the smell of rubbish and how the community participates in waste management. The method in this research was a survey method with analysis techniques using descriptive methods. The results of the research showed that the community had participated in the form of rubbish shelter with a percentage of 56.6%, rubbish collection with a percentage of 56.6%, and the level of community participation was high with a percentage of 93.3%. The conclusion of the community in Tlekung Village is the level of participation is high in reducing the smell of rubbish and participating in the management of waste into methane gas. From the results of community participation in helping to manage waste, the community gets the free flow of methane gas from TPA Tlekung.